Identification of mutation in synaptonemal complex protein 3 gene and its interaction with methotrexate in case of breast cancer in female Albino mice - Shardhanjali Sinha; Aniket Kumar; Ashis Kumar Ghosh (Wolters Kluwer -Medknow Publications, 2023)
Introduction: To date, a few research studies have reported the significance of synaptonemal complex protein 3 (SYCP3) gene mutation in breast cancer. The present study aims to identify SYCP3 gene mutation in the case of breast cancer in female Albino mice and to assess the interaction of mutated SYCP3 protein with the drug methotrexate (MTX). Materials and Methods: To induce breast cancer in female Albino mice, the carcinogen 7, 12-Dimethylbenz (a) anthracene was used. The blood samples were collected from mice that developed breast cancer and a polymeric chain reaction was performed to check the mutation in the SYCP3 gene with a specific primer. Thereafter, whole genome sequencing was performed, which was further validated by referring to online bioinformatics databases and tools. Results: After performing whole genome sequencing and translation, the normal SYCP3 sequence was compared with the mutated one, where a frameshift mutation was observed in which 1 bp was deleted at position (643delA) (Al ─A that codes for ILE at position 197 (ILE ─I in protein sequence. The free binding energy released by the interaction of MTX with the mutated SYCP3 protein (MET, GLU, GLN, GLU, and ILE) was lower (−3.09 Kcal/mol) than that of the interaction of normal SYCP3 protein. Therefore, the mutated SYCP3 and MTX interaction can be considered the best molecular docking interaction. Conclusion: The present study is imperative to recognize a potential therapeutic agent to cure breast cancer. It ultimately paves the way to modify the existing line of treatment for different pathological conditions of breast cancer and promote personalized medicine.